Epitaxial K(0.5)Na(0.5)NbO(3) thin films by aqueous chemical solution deposition - Pham, Ky-Nam (R Soc Open Sci, 2019)
We report on an environmentally friendly and versatile aqueous chemical solution deposition route to epitaxial K(0.5)Na(0.5)NbO(3) (KNN) thin films. The route is based on the spin coating of an aqueous solution of soluble precursors on SrTiO(3) single crystal substrates followed by pyrolysis at 400°C and annealing at 800°C using rapid thermal processing. Strongly textured films with homogeneous thickness were obtained on three different crystallographic orientations of SrTiO(3). Epitaxial films were obtained on (111) SrTiO(3) substrates, while films consisting of an epitaxial layer close to the substrate followed by an oriented polycrystalline layer were obtained on (100) and (110) SrTiO(3) substrates. A K(2)Nb(4)O(11) secondary phase was observed on the surface of the thin films due to the evaporation of alkali species, while the use of an NaCl/KCl flux reduced the amount of the secondary phase. Ferroelectric behaviour of the films was investigated by PFM, and almost no dependence on the film crystallographic orientation was observed. The permittivity and loss tangent of the films with the NaCl/KCl flux were 870 and 0.04 (100-orientation) and 2250 and 0.025 (110-orientation), respectively, at 1 kHz.